Global Transcriptome Analysis Reveals Distinct Aluminum-Tolerance Pathways in the Al-Accumulating Species Hydrangea macrophylla and Marker Identification. - Haixia Chen; Changping Lu; Hui Jiang; Jinhui Peng (PLoS ONE)
Hydrangea (Hydrangea macrophylla) is a well known Al-accumulating plant, showing a high level of aluminum (Al) tolerance and accumulation. Although the physiological mechanisms for detoxification of Al and the roles of Al in blue hydrangea sepals have been reported, the molecular mechanisms of Al tolerance and accumulation are poorly understood in hydrangea. In this study, we conducted a genome-wide transcriptome analysis of Al-response genes in the roots and leaves of hydrangea by RNA sequencing (RNA-seq). The assembly of hydrangea transcriptome provides a rich source for gene identification and mining molecular markers, including single nucleotide polymorphism (SNP) and simple sequence repeat (SSR). A total of 401,215 transcripts with an average length of 810.77 bp were assembled, generating 256,127 unigenes. After annotation, 4,287 genes in the roots and 730 genes in the leaves were up-regulated by Al exposure, while 236 genes in the roots and 719 genes in the leaves were down-regulated, respectively. Many transporters, including MATE and ABC families, were involved in the process of Al-citrate complex transporting from the roots in hydrangea. A plasma membrane Al uptake transporter, Nramp aluminum transporter was up-regulated in roots and leaves under Al stress, indicating it may play an important role in Al tolerance by reducing the level of toxic Al. Although the exact roles of these candidate genes remain to be examined, these results provide a platform for further functional analysis of the process of detoxification of Al in hydrangea.